2020
DOI: 10.1186/s43170-020-00003-w
|View full text |Cite
|
Sign up to set email alerts
|

Terminal drought effect on sugar partitioning and metabolism is modulated by leaf stay-green and panicle size in the stem of sweet sorghum (Sorghum bicolor L. Moench)

Abstract: Background: The benefits of leaf stay-green for maintaining grain filling in sorghum under drought was largely demonstrated. However, its role in the stability of a dual production (grain, stem sugar) in tall sweet sorghum remains to be elucidated. This study aimed to analyze the impact of a post-anthesis drought on sugar accumulation along stem internodes in sweet and tall West-African sorghum with variable leaf stay-green and grain yield abilities. Methods: Four accessions with similar phenology were studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 28 publications
(39 reference statements)
2
8
0
1
Order By: Relevance
“…Crops respond to drought stress conditions to varying extents through different mechanisms. Drought tolerance involves physiological and molecular mechanisms (Sabadin et al 2012 ) for activation of relevant genes and pathways, allocation of energy and resource for cellular functioning, and modification in stomatal conductance and transpiration as well as for increasing water use efficiency and promoting stay-green (Tovignan et al 2020 ). Thus, drought tolerance is a result of diverse physico-chemical alterations (Sehgal et al 2018 ; Impa et al 2019 ) leading to fitness costs that hampers crop productivity.…”
Section: The Effect Of Drought Stress On Sorghum Grain Yieldmentioning
confidence: 99%
“…Crops respond to drought stress conditions to varying extents through different mechanisms. Drought tolerance involves physiological and molecular mechanisms (Sabadin et al 2012 ) for activation of relevant genes and pathways, allocation of energy and resource for cellular functioning, and modification in stomatal conductance and transpiration as well as for increasing water use efficiency and promoting stay-green (Tovignan et al 2020 ). Thus, drought tolerance is a result of diverse physico-chemical alterations (Sehgal et al 2018 ; Impa et al 2019 ) leading to fitness costs that hampers crop productivity.…”
Section: The Effect Of Drought Stress On Sorghum Grain Yieldmentioning
confidence: 99%
“…Drought stress can negatively affect sorghum development and yield depending on its intensity and the stage at which it occurs. Previous studies reported that drought occurring at post-flowering stage affect negatively sorghum mainly on grain yield, biomass and stem sugar accumulation [13][14][15][16]. However, very little is known about the effect of early drought stress on sorghum development and production stages.…”
Section: Introductionmentioning
confidence: 99%
“…At the physiological level, it can disrupt metabolism, thereby affecting crop yields. The metabolic process is characterized by the formation of compounds in response to drought conditions, such as sugar [44,45], glycine-betaine [46,47], proline [48,49], and ABA [50,51].…”
Section: Water Deficitmentioning
confidence: 99%